GhSNAP33, a t-SNARE Protein From Gossypium hirsutum, Mediates Resistance to Verticillium dahliae Infection and Tolerance to Drought Stress - Wang, Ping; Sun, Yun; Pei, Yakun; Li, Xiancai; Zhang, Xueyan; Li, Fuguang; Hou, Yuxia (Frontiers in Plant Science, 2018)
Abstract Soluble N-ethylmaleimide-sensitive fusion protein attachment protein receptor (SNARE) proteins mediate membrane fusion and deliver cargo to specific cellular locations through vesicle trafficking. Synaptosome-associated protein of 25 kDa (SNAP25) is a target membrane SNARE that drives exocytosis by fusing plasma and vesicular membranes. In this study, we isolated GhSNAP33, a gene from cotton (Gossypium hirsutum), encoding a SNAP25-type protein containing glutamine (Q)b- and Qc-SNARE motifs connected by a linker. GhSNAP33 expression was induced by H2O2, salicylic acid, abscisic acid, and polyethylene glycol 6000 treatment and Verticillium dahliae inoculation. Ectopic expression of GhSNAP33 enhanced the tolerance of yeast cells to oxidative and osmotic stresses. Virus-induced gene silencing of GhSNAP33 induced spontaneous cell death and reactive oxygen species accumulation in true leaves at a later stage of cotton development. GhSNAP33-deficient cotton was susceptible to V. dahliae infection, which resulted in severe wilt on leaves, an elevated disease index, enhanced vascular browning and thylose accumulation. Conversely, Arabidopsis plants overexpressing GhSNAP33 showed significant resistance to V.dahliae, with reduced disease index and fungal biomass and elevated expression of PR1 and PR5. Leaves from GhSNAP33-transgenic plants showed increased callose deposition and reduced mycelia growth. Moreover, GhSNAP33 overexpression enhanced drought tolerance in Arabidopsis, accompanied with reduced water loss rate and enhanced expression of DERB2A and RD29A during dehydration. Thus, GhSNAP33 positively mediates plant defense against stress conditions and V.dahliae infection, rendering it a candidate for the generation of stress-resistant engineered cotton.